Analysis of the x-ray diffraction, etching, luminescence, photoconductivity, thermal and dielectric properties of an ADP crystal influenced by the bimetallic additive sodium metasilicate (Na2SiO3). (20th October 2016) - Anis, Mohd; Hussaini, S S; Shirsat, M D; Shaikh, R N; Muley, G G
Abstract: The present communication is focused on an investigation of the structural, optical, electrical and thermal properties of a sodium metasilicate (SMS)-doped ammonium dihydrogen phosphate (ADP) crystal. The slow evaporation solution technique has been adopted to grow the crystal with an optimum size of (10 × 6 × 4) mm 3 . The powder x-ray diffraction (PXRD) technique has been employed to confirm the crystalline nature, crystal structure and cell parameters of the crystal (a = b = 7.53 (±0.01) Ǻ, c = 7.59 (±0.03) Ǻ). The color-centered photoluminescence nature of the SMS-doped ADP crystal has been examined in the visible region of interest at an emission wavelength of 375 nm. Its frequency-dependent dielectric response has been investigated with reference to a pure ADP crystal to explore optoelectronic device applications. The thermal stability of the crystal has been examined by means of simultaneous thermogravimetric and differential thermal analysis, and its surface quality has been investigated by means of etching studies. Finally, photoconductivity studies have been employed to determine the nature of photoconductivity in the crystal.